Pengaruh Kepercayaan dan Komitmen Terhadap Loyalitas Nasabah Bank Syariah Indonesia di Kota Medan - Adelina Lubis; Ihsan Effendi; Dhian Rosalina (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to analyze whether trust has a partial effect on customer loyalty of Bank Syariah Indonesia in Medan City, whether commitment has a partial effect on customer loyalty at Bank Syariah Indonesia in Medan City. transactions at Indonesian Islamic banks, savings customers who have used bank services for at least 1 year and savings customers who use the services directly. The analysis technique used in this research is descriptive analysis, and multiple linear regression test. The results of this study indicate that the trust variable partially has a positive and significant effect on customer loyalty of Bank Syariah Indonesia in Medan City, the commitment variable partially has a positive and significant effect on customer loyalty of Bank Syariah Indonesia in Medan City.